Human renal adipose tissue from normal and tumor kidney: ITS influence on renal cell carcinoma - Bruna, Flavia Alejandra (2019)
Tumor cells can interact with neighboring adipose tissue. We evaluated components present in human adipose explants from normal (hRAN) and kidney cancer (hRAT) tissue, and we evaluated the effects of conditioned media (CMs) from hRAN and hRAT on proliferation, adhesion and migration of tumor and non- tumor human renal epithelial cell lines. In addition, we evaluated the expression of AdipoR1, ObR, CD44, vimentin, pERK and pPI3K on cell lines incubated with CMs. hRAN were obtained from healthy operated donors, and hRAT from patients who underwent a nephrectomy. hRAT showed increased levels of versican, leptin and ObR; and decreased levels of perilipin, adiponectin and AdipoR1, compared to hRAN. Cell lines showed a significant decrease in cell adhesion and increase in cell migration after incubation with hRAT-CMs vs. hRAN- or control-CMs. Surprisingly, HK-2, 786- O and ACHN cells showed a significant decrease in cell migration after incubation with hRAN-CMs vs. control-CMs. No difference in proliferation of cell lines was found after 24 or 48 h of treatment with CMs. AdipoR1 in ACHN and Caki-1 cells decreased significantly after incubation with hRAT-CMs vs. hRAN-CMs and control-CMs. ObR and CD44 increased in tumor line cells, and vimentin increased in non-tumor cells, after incubation with hRAT-CMs vs. hRAN-CMs and control-CMs. We observed an increase in the expression of pERK and pPI3K in HK-2, 786-O and ACHN, incubated with hRAT- CMs. In conclusion, results showed that adipose microenvironment can regulate thebehavior of tumor and non tumor human renal epithelial cells.